Islam dan Negara-Bangsa: Melacak Akar-akar Nasionalisme Indonesia - Jajat Burhanudin (Studia Islamika, 2004)
In this book, the main focus of discussion is the changes and development in Mulims' way of thinking about their identity. Islam is placed in an important position, with an historio-cultural basis, which is then presented as a strength in the formation of nationalism. The term bilad al-jawah appears as a form of community identity. Bilad al-jawah, also called "the land below wind", was a geographical parameter that referred to the Muslim Archipelago as a community with a strong level of thought, exchange and cultural communication (ecumene).DOI: 10.15408/sdi.v11i1.656